Deconstructing Gender Identities: A Feminist Poststructuralist Study of A Thousand Splendid Suns by Khaled Hosseini - Safoora Batool Syed; Moazzam Ali Malik; Dildar Ahmed (Journal of Peace, Development and Communication, 2023)
This study takes a poststructuralist stance on gender construction in A Thousand Splendid Suns and explores how the inextricably interwoven gender discourses of the selected text result in negotiated gender identities and power relations. The complexity of competing discourses results in the plurality of meaning where gender 'signifier' itself becomes a site of struggle for the multitude of 'signified'. With this poststruturalist viewpoint that treats gender identities as a fluid and negotiated phenomenon, the current study employs the theoretical framework of Feminist Poststructuralist Discourse Analysis (FPDA) to study the dynamic feminine identities in A Thousand Splendid Suns. It is envisaged that the current study will provide a new lens for looking at gender identities and power relations as a multi-dimensional and pluralistic phenomenon.